Catalytic removal of propene and toluene in air over noble metal catalyst. Issue 1 (March 2014) - Benard, S.; Ousmane, M.; Retailleau, L.; Boreave, A.; Vernoux, P.; Giroir-Fendler, A.
Abstract : In this paper we present the study of catalytic oxidation of volatile organic compound (VOC) traces in air over Pt/γ-Al2O3 catalysts. The study was carried out using a laboratory fixed-bed catalytic reactor (FBCR) with catalytic oxidation of propene and toluene as model reactions. For better understanding of catalytic activity in a FBCR, the influence of operating parameters such as of platinum (Pt) loading, total gas flow rate, VOC concentration, and oxygen content were studied. The results showed that catalytic activity increases with increase in VOC concentration and a decrease in total gas flow rate. This displayed behaviour is instrumental to working at a low temperature region for complete oxidation of volatile organic compounds.